Strategic Planning for Development of Aek Sijorni Natural Bathing Tourism Objects at the Tourism Office of South Tapanuli Regency - Rinaldi, Ahmad; Nasution, Muhammad Husni Thamrin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research was conducted due to the reduced number of visitors who come to Aek Sijorni's natural bath. The cause of the reduced number of visitors coming to Aek Sijorni's natural baths is the lack of promotion carried out by the South Tapanuli Regency Tourism Office, the lack of communication between the South Tapanuli Regency Tourism Office and the local community, then there are two management parties, namely the South Tapanuli Regency Tourism Office and the private sector. Even though Aek Sijorni's natural bath has the potential for a very good tourist spot. Apart from the retribution, recreation areas are the second largest contributor to South Tapanuli Regency's Original Regional Revenue. This research was conducted using descriptive qualitative research. The data collection technique was conducted by interview, observation, and documentation. The sampling technique was carried out by purvosive sampling. The data analysis using SWOT analysis. The initial step taken is to analyze the internal and external environment to find out the strengths, weaknesses, opportunities, and threats in the development of Aek Sijorni Natural Baths Tourism Object. From the results of the study, it can be concluded that in strategic planning for the development of Aek Sijorni Natural Baths, an alternative strategy based on SWOT analysis is the SO (Strengths-Opportunities) strategy, namely improving the quality of tourism objects, improving facilities and infrastructure, and optimizing media and technology. ST (Strengths-Threats) strategy is to increase the natural potential, facilities, and tourism activities to become an attraction for Aek Sijorni Natural Baths Tourism Object, and to increase supervision of irresponsible tourists. The WO (Weaknesses-Opportunities) strategy is to increase the human resources of employees and managers, and improve services to tourists. WT (Weaknesses-Threats) strategy, namely increasing cooperation with investors and related parties, and increasing promotions.